Studi Literatur: Penerapan Metode Tilawati dalam Pembelajaran Membaca Al-Qur’an - Sidqi, Ansori; Kinasih, Anya Dani (YASIN, 2025)
The ability to read the Quran in a proper and tajwid-compliant manner is an important foundation in Islamic education. One method that is widely applied in Indonesia to improve the quality of Quranic reading among students is the Tilawati method. This article is a literature review that aims to compile and analyze research findings related to the effectiveness and challenges in the implementation of the Tilawati method in various Islamic educational institutions. Through a qualitative approach and literature study technique, data were collected from scientific journals published over the last five years (2020–2025) that are relevant to the theme. The results indicate that the Tilawati method has high effectiveness in improving Quranic reading ability (85%), recognizing hijaiyah letters (6%), enhancing memorization (6%), and generally improving learning outcomes (3%). However, its implementation faces several obstacles, including low student motivation (40%), time limitations (20%), lack of facilities (20%), and insufficient teacher understanding of this method (20%). This study recommends the need for enhanced teacher training, provision of adequate facilities, and strategies to build student motivation in Quranic learning. With appropriate support, the Tilawati method can be an effective solution in sustainable Quranic literacy education.